2011
DOI: 10.1083/jcb.201101050
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin 3 functions as an ER Ca2+ channel, hemichannel, and gap junction to promote osteoblast differentiation

Abstract: Pannexin 3 functions as an essential protein for Ca2+ and ATP transport and cell–cell communication during osteoblast differentiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
196
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(203 citation statements)
references
References 68 publications
7
196
0
Order By: Relevance
“…Immunofluorescence results showed that Panx3 was expressed in the cell membrane and cytoplasm (Fig. 2C), which was consistent with previous study that Panx3 is expressed in plasma membrane and diffusely in the cytosol acting as and ER Ca 2+ channel 19, 21.…”
Section: Resultssupporting
confidence: 92%
“…Immunofluorescence results showed that Panx3 was expressed in the cell membrane and cytoplasm (Fig. 2C), which was consistent with previous study that Panx3 is expressed in plasma membrane and diffusely in the cytosol acting as and ER Ca 2+ channel 19, 21.…”
Section: Resultssupporting
confidence: 92%
“…Panx3 has been implicated in a number of cellular processes including its involvement in the regulation of keratinocyte and chondrocyte proliferation and differentiation, participation in Ca 2+ leak from the endoplasmic reticulum and the promotion of bone development. 5,8,9,36 The participation of NO signaling events in a number of these processes has also been well documented. For example, NO promotes bone and cartilage development by influencing osteoblast and chondrocyte differentiation, processes that are influenced by activation of Panx3 channels at the plasma membrane and ER.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Importantly, functional analysis of the channel properties of Panx1 and Panx3 have revealed a significant role for these channels in releasing ATP to extracellular spaces 7,8 and facilitating Ca 2+ influx into the cytosol. 9,10 Panx1 has been the most studied as it is more ubiquitously expressed than Panx2 (predominantly found in the CNS) and Panx3 (found in skin, bone, cartilage, and mammary gland). 1,11 An important physiological role for Panx1 is the regulation of vascular smooth muscle cell constriction in resistance arteries through an interaction with the α1-adrenergic receptor.…”
Section: Introductionmentioning
confidence: 99%
“…13 Panx3 mRNA and protein are expressed primarily in skin, chondrocytes, and osteoblasts. [14][15][16] While there is some information on the relative mRNA and protein levels of different Panxs over the course of embryonic development and postnatal life, the extent of co-distribution of different Panxs at these critical stages remains lacking for many tissues.…”
Section: Pannexin Distribution At the Tissue And Cellular Levelmentioning
confidence: 99%